Faktor-faktor yang mempengaruhi perilaku disfungsional audit pada auditor: Systematic Literature Review - Fitria Heny Widyastuti; Yulia Saftiana; Yusnaini Yusnaini; Hasni Yusrianti (Owner : Riset dan Jurnal Akuntansi, 2025)
Dysfunctional audit behavior is deviant behavior carried out by an auditor in the form of manipulation, fraud or deviation from standards. Behavioral deviations that are usually carried out by auditors include reporting audit time with a total time shorter than the actual time, changing and/or stopping procedures that have been established in the implementation in the field, obtaining evidence that is less accurate, processing less accurately, and errors in the audit stages. This study aims to determine the main factors that influence dysfunctional audit behavior carried out by auditors. The method used in this study is the literature review (SLR) method. Research data were obtained from indexed journals Q1, Q2, Q3 and sinta 2 from emerald, proquest, and simantic scholar. This review analyzed 24 articles on dysfunctional audit behavior in the world published from 2010-2024. Most of the articles published use a quantitative approach and focus on public accounting firms. The main findings of this study found that the most influential factors (determinants) in dysfunctional audit behavior are time budget pressure, locus of control, gender, turnover intention, performance evaluation, task complexity, auditor work experience, employee performance, client interests, and organizational and professional commitment. Furthermore, further research should also consider the need for exploration, reflection, and asking more critical questions, not from the existing side. For example, asking again how the head of the Public Accounting Firm conducts performance assessments to reduce dysfunctional audit behavior and research on dysfunctional audit behavior is not only in the Public Accounting Firm but can be done in other public sectors.